A novel high-strength and highly corrosive biodegradable Fe-Pd alloy: Structural, mechanical and in vitro corrosion and cytotoxicity study - Čapek, Jaroslav; Msallamová, Šárka; Jablonská, Eva; Lipov, Jan; Vojtěch, Dalibor (Materials science & engineering. C, Materials for biological applications, 2017)
Recently, iron-based materials have been considered as candidates for the fabrication of biodegradable load-bearing implants. Alloying with palladium has been found to be a suitable approach to enhance the insufficient corrosion rate of iron-based alloys. In this work, we have extensively compared the microstructure, the mechanical and corrosion properties, and the cytotoxicity of an FePd2 (wt%) alloy prepared by three different routes - casting, mechanical alloying and spark plasma sintering (SPS), and mechanical alloying and the space holder technique (SHT). The properties of the FePd2 (wt%) were compared with pure Fe prepared in the same processes. The preparation route significantly influenced the material properties. Materials prepared by SPS possessed the highest values of mechanical properties (CYS~750-850MPa) and higher corrosion rates than the casted materials. Materials prepared by SHT contained approximately 60% porosity; therefore, their mechanical properties reached the lowest values, and they had the highest corrosion rates, approximately 0.7-1.2mm/a. Highly porous FePd2 was tested in vitro according to the ISO 10993-5 standard using L929 cells, and two-fold diluted extracts showed acceptable cytocompatibility. In general, alloying with Pd enhanced both mechanical properties and corrosion rates and did not decrease the cytocompatibility of the studied materials.
Keywords: železo; testování materiálů; Biodegradability; zatížení muskuloskeletálního systému; Biocompatible Materials; slitiny; biokompatibilní materiály; Corrosion; Palladium; Iron; Lead; Weight-Bearing; Alloys; Powder Metall.; olovo; Spark plasma sintering; koroze; Materials Testing